"But Aren't Cults Bad?": Active Learning, Productive Chaos, and Teaching New Religious Movements. (April 2015) - Zeller, Benjamin E.
Abstract This article considers the challenges inherent when teaching about new religious movements ("cults"), how successful instructors have surmounted them, and how teacher‐scholars in other fields of religious studies can benefit from a discussion of the successful teaching of new religions. I note that student‐centered pedagogies are crucial to teaching new religions, particularly if students disrupt and defamiliarize the assumed and reified categories of "cult" and "religion." I argue that what works in a classroom focusing on new religious movements will work more broadly in religious studies classrooms, since the challenges of the former are reproduced in the latter.